Bendera Bajak Laut di Negara Bajakan: Semiotika Perlawanan terhadap Nasionalisme Palsu - Mohammad Fikri; Fajar Ainol Yakin; Muhammad Muslim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The phenomenon of the use of the Jolly Roger symbol, a pirate flag, in the anime One Piece by Indonesians during Independence Day in August 2025 gave rise to an interesting symbolic battle between representations of the people and the state. In this context, this article explores how popular cultural symbols can be used as a tool of visual resistance against state nationalism that is considered to be losing legitimacy, especially in the increasingly connected digital era. The Jolly Roger symbol, known as the pirate flag, is not only seen as a symbol of freedom in pop culture, but also as an expression of rejection of nationalist narratives that are considered